EPISTEMOLOGICAL TRENDS OF THE GRADUATE COURSE IN PHYSICAL EDUCATION AT THE REGIONAL UNIVERSITY OF BLUMENAU (Fiep Bulletin - online, 2011)
Studies have been conducted since the 70s to analyze the scientific production of education in Brazil, uncovering the trends in research. The scenario of the courses of physical education in the State of Santa Catarina, research and educational practices, a technical context can be observed, showing the prospect of a teaching system sustained by fragmented and decontextualized practices, of a critical transforming and revolutionary educational proposal. The aim of this study is to analyze the development of scientific output of Physical Education in the seminars and forums offered by the Regional University of Blumenau in the period of 1999 to 2009, whereas that the epistemological basis implicit in the undergraduate research allow and / or determine the educational practice category historically. For this matter a qualitative research was conducted, taking the paradigmatic scheme of Sanchez Gamboa (1987) the components needed for the study analysis. The mapping showed a total of 40 abstracts of proceedings, (28) featured an empirical-analytic approach, making a percentage of 70% of the sample, (09) in the phenomenological – hermeneutic approach, and 22.5%, (03) works in Critical approach – Dialectic representing 7.5% . The results show that empirical-analytic studies are the most commonly performed, which is characterized as a positivist line of approach, which quantitative techniques are predominantly used, in which there is a control of variables.
Keywords: Physical Education; Epistemology; Scientific Production